SKEETER’S STRUGGLE FOR LIFE EQUALITY OF BLACK WOMEN IN THE HELP FILM - Nor Holis; Ratna Asmarani (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
The Help is a film  that is adopted from Kathryn Stockett’s novel with the same title. It tells about a young white woman named Skeeter who wants to make black and white people live equally in the society. This research aims to analyze Skeeter’s struggle for life equality between black and white people. In order to analyze it, the writer applies Adler’s individual psychology to the data from the film such as dialogues, monologue and scenes. Furthermore, this research is assumed to be useful for the following researchers with the same topic or idea. Adler’s individual psychology is used to analyze Skeeter’s life of style and her struggle for superiority or striving for superiority. Hence, those aspects would give understanding how Skeeter fights for black people’s life. This research concludes that Skeeter struggles for making black people’s life better. It is influenced by her childhood experience that is called style of life and social inequality. Her style of life encourages her to do an action to make black people well-accepted in the society. Therefore, her struggle is also called as striving for superiority that is not for herself but for social interest.